Application of Intra-articular Corticosteroid Injection in Juvenile Idiopathic Arthritis - Li, Sha; Zhang, Wei; Lin, Yan (Frontiers in Pediatrics, 2022)
Juvenile idiopathic arthritis (JIA) is one of the common rheumatic diseases in paediatrics. Persistent synovitis and joint pain cause reduced range of motion, deformity and gait interruption, which are important reasons for children’s disability and a decline in their quality of life. Rheumatology experts have explored good treatment strategies, among which intra-articular corticosteroid injections (IACIs) targeting joints can greatly reduce these systemic adverse reactions while still obtaining local anti-inflammatory effects. Local inhibition of synovitis by the use of steroid hormones in a joint cavity can avoid or reduce adverse reactions of systemic therapy, prevent or treat leg length variance and joint contracture, solve Baker’s cyst, improve tenosynovitis, promote physical therapy and rehabilitation, make gait change smoothly, relieve pain and restore joint function. Given the importance of IACIs in treating JIA, this paper reviewed the case selection, drug injection, dose selection, current anaesthesia and injection techniques, the efficacy, recurrence and influencing factors of IACIs, the management of physiotherapy intervention post-injection, the application of ultrasound guidance and the safety and complications of IACIs in children with JIA. This study aims to guide the use of IACIs for the best approach throughout the review.